Feeding Habits and Nutritional Status of Toddlers with Weight Faltering in Sukadana Village - Maulin Halimatunnisa'; Vera Yulandasari; D. Mustamu Qamal Pa’ni; Aniza Febyana; Frisma Lita; Iwan Wahyudi; Lalu Hersika Asmawariza; Erwin Wiksuarini (NERS Jurnal Keperawatan, 2026)
Weight faltering in children aged 6–24 months is a major nutritional problem that can impair growth and development. This condition is closely associated with inappropriate Infant and Young Child Feeding (IYCF) practices, particularly inadequate complementary feeding. Appropriate IYCF is essential to ensure adequate nutrient intake and support optimal nutritional status during this critical period. To determine the relationship between infant and young child feeding (IYCF) habits and the nutritional status of children aged 6 and 24 months in Sukadana Village. The study design used a cross-sectional correlation. The study sample consisted of 54 people using a purposive sampling technique. The study variables were feeding habits and toddler nutritional status. The instruments used were the Child Growth Chart and a questionnaire IYCF Patterns. Data analysis used the chi-square test. Most caregivers practiced adequate IYCF (61.1%), while more than half of the children were classified as underweight (55.6%). Statistical analysis showed a significant association between IYCF practices and children’s nutritional status (p = 0.007). The findings indicate that appropriate feeding practices are closely related to better nutritional outcomes in toddlers. Inadequate feeding behaviors may contribute to undernutrition despite the availability of food, highlighting the importance of caregiver knowledge and skills in feeding management. This study underscores the importance of Infant and Young Child Feeding practices in relation to the nutritional status of children aged 6–24 months. The findings support the need for strengthened nutrition education and community-based feeding efforts to promote optimal child growth.